Recent expansion of the Atlantic cownose ray (Rhinoptera bonasus) into Bermudian waters - Ajemian, Matthew J.; Hampton, Cecilia M.; Coleman, Lauren M.; Pitt, Joanna M.; Smith, Struan R.; Jones, Christian M.; Phillips, Nicole M. (Frontiers in Fish Science, 2024)
Cownose rays (Family Rhinopteridae) are highly migratory pelagic rays that are generally restricted to continental shelves. Despite hundreds of years of natural history records, cownose rays have never been reported in Bermuda, an atoll-like coral reef ecosystem that is separated from the continental mainland United States by approximately 1000 km. Here we compile evidence that the Atlantic cownose ray (Rhinoptera bonasus) has recently established in Bermuda, supported by both morphological and genetic data. Potential ecological and inter-specific competition concerns are presented as well as probable physical mechanisms that facilitated this recent and presumed range expansion.